The Influence of Arts Education on the Formation of Adolescent Cultural Identity - Raihan Saputra; Farhan Saputra; M. Ridho Mahaputra (Greenation Education and Culture Review, 2024)
Article about the analysis of the influence of identity formation and art education on cultural identity. The purpose of this writing is to build a hypothesis about the influence between variables that can later be used for further research. The research method used is descriptive qualitative. The data used in this descriptive qualitative approach comes from previous research that is relevant to this research and is obtained from online academic media such as Taylor & Francis, Scopus Emerald, Web of Science, Sinta Journal, DOAJ, EBSCO, Google Scholar, and digital reference books. The results of this article are: 1) Identity formation has an influence on cultural identity; 2) Art education has an influence on cultural identity.